2018
DOI: 10.1016/j.jagp.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Subjective but Not Objective Sleep is Associated with Subsyndromal Anxiety and Depression in Community-Dwelling Older Adults

Abstract: Subclinical levels of late-life anxiety and depression have distinct associations with subjective sleep disturbance. Findings implicate subjective measures of sleep quality and daytime sleepiness as stronger trait markers for subthreshold psychiatric symptoms than objective sleep biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Similarly, the sleep, cognitive and inflammatory data presented in this study were assessed at one time-point, rather than specifically assessing the prior evening’s sleep and the following morning’s inflammatory markers. We used subjective sleep measures, which, although they may be subject to recall biases, have been reported in psychiatric populations to correlate significantly with objective sleep measures (73) and physical/mental health outcomes (59) as well as having clinical utility in diagnosing and treating sleep disorders (14, 74). Although we did not use a validated sleep questionnaire such as the Pittsburgh Sleep Quality Index, the measures did include key features of sleep that overlap with clinical definitions of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the sleep, cognitive and inflammatory data presented in this study were assessed at one time-point, rather than specifically assessing the prior evening’s sleep and the following morning’s inflammatory markers. We used subjective sleep measures, which, although they may be subject to recall biases, have been reported in psychiatric populations to correlate significantly with objective sleep measures (73) and physical/mental health outcomes (59) as well as having clinical utility in diagnosing and treating sleep disorders (14, 74). Although we did not use a validated sleep questionnaire such as the Pittsburgh Sleep Quality Index, the measures did include key features of sleep that overlap with clinical definitions of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…No study has been su ciently large to show a statistically signi cant modifying effect of sleep quality and anxiety in an overall healthy population. However, there was another study found that poor sleep quality was associated with both depression and anxiety, whereas only daytime sleepiness was associated with anxiety symptoms in older adults [34].…”
Section: Discussionmentioning
confidence: 93%
“…Few studies have been sufficiently large to show a statistically significant modifying effect of sleep quality and anxiety in an overall healthy population. However, another study found that poor sleep quality was associated with both depression and anxiety, whereas only daytime sleepiness was associated with anxiety symptoms in older adults [43].…”
Section: Discussionmentioning
confidence: 95%